Could evidence-based medicine results be reproduced in real-world clinical practice? - S. Yu. Martsevich; N. P. N.P. Kutishenko (Кардиоваскулярная терапия и профилактика, 2008)
The authors review the principal achievements of evidence-based medicine in regard to cardiovascular event risk reduction. The medications improving life prognosis are listed. The conditions for reproducing evidence-based medicine results in real5world clinical practice are discussed. One of these conditions is the compliance to international clinical guidelines and use of high-quality medications.